Creative Self‐Efficacy and Metacognitive Feelings as Sources of Information when Generating, Evaluating, and Selecting Creative Ideas: A Metacognitive Perspective. (29th July 2022) - Puente‐Díaz, Rogelio; Cavazos‐Arroyo, Judith
ABSTRACT: In one study, we examined the relationships between pre‐task creative self‐efficacy, post‐task creative confidence, self‐rated and judges‐rated creativity evaluations, metacognitive feelings, and idea selection under a metacognitive framework. Four hundred and fourteen college students were asked to complete a divergent thinking problem in the domain of marketing and completed several questionnaires measuring pre‐task creative self‐efficacy, post‐task creative confidence, idea evaluation and selection, and metacognitive feelings. Independent judges evaluated the creativity of each idea generated and ranked ideas from the most to the least creative. Results showed positive relationships between pre‐task creative self‐efficacy and post‐task creative confidence, self‐ and judges‐rated creativity evaluations and metacognitive feelings. In addition, metacognitive feelings and self‐rated creative evaluations predicted post‐task confidence. We also observed evidence for positive connections between metacognitive feelings and self‐rated evaluations and greater probability of choosing the first idea brought to mind as the best idea than what was expected by chance. The implications of the results were discussed.